Music Interventions and Child Development: A Critical Review and Further Directions - Dumont, Elisabeth; Syurina, Elena V.; Feron, Frans J. M.; van Hooren, Susan (Frontiers in Psychology, 2017)
Research on the impact of music interventions has indicated positive effects on a variety of skills. These findings suggest musical interventions may have further potential to support educational processes and development of children. This paper reviews the latest evidence on the effect of musical interventions on the development of primary school-aged children. Four electronic databases were searched from January 2010 through June 2016 using music, music instruction, music education, music lesson, music training, development, child, student, and pupil as key words for the search. Two reviewers independently evaluated the studies to determine whether they met the stated inclusion criteria. Studies were compared on study setup, methodological quality, intervention components, outcome variables and efficacy. A review of these selected studies (n = 46) suggestive beneficial effects of music intervention on development of children, although clear conclusions cannot be drawn. Possible influencing factors that might contribute to the outcome of intervention are reviewed and recommendations for further research are made.